Comparison of acidic and basic ionic liquids effects on dispersion of alumina particles in Pebax composite membranes for CO2/N2 separation: Experimental study and molecular simulation. Issue 5 (October 2021) - Kojabad, Mahdi Elyasi; Babaluo, AliAkbar; Tavakoli, Akram; Sofla, Reza Lotfi Mayan; Kahnamouei, Haniyeh Golizadeh
Abstract: In this study, two types of acidic and basic ionic liquids (ILs) were used to modify the γ-Al2 O3 particles. Different amounts of modified particles were added to the poly (ether-block-amide) (Pebax) polymeric matrix, and various composite membranes were prepared. FTIR (Fourier transform infrared), SEM (scanning electron microscopy), XRD (X-ray diffraction), DSC (differential scanning calorimetry), tensile and gas permeation analyses, as well as molecular simulations, were used to study the effect of ILs on the structure of membranes and their performances. The results indicated that ILs prevented well the sedimentation and agglomeration of particles through the electrostatic and steric forces. The electrostatic forces were more effective than steric forces. In addition to improving membrane separation performance and overcoming the trade-off limit, the modification of γ-Al2 O3 particles has improved membranes mechanical strength. The comparison of ILs performances showed that the acidic IL had a better effect on the particle dispersion than the basic one. The CO2 permeability and CO2 /N2 selectivity in the membrane containing 10 wt% acidic IL-modified particles increased about 47% and 124%, respectively, compared to the pure Pebax membrane. The molecular simulation confirmed the experimental results and showed that the employed ILs had different effects on the diffusivity and solubility coefficients of CO2 molecules in the membranes. Based on simulation results, the acidic IL improved the solubility coefficient by 95%, and the basic IL enhanced the diffusivity coefficient by 71%. Graphical Abstract: ga1 Highlights: The effect of acidic and basic ILs on the dispersion of particles in the polymeric matrix studied for CO2 /N2 separation. ILs prevented well the sedimentation and agglomeration of particles through the electrostatic and steric forces. The electrostatic forces were more effective than steric forces. The acidic IL had a better effect on the particle dispersion than the basic one. The optimum membrane surpassed the 2008 Robson upper bound line.